PEMBERDAYAAN PEREMPUAN MELALUI KERAJINAN KESED BERBAHAN LIMBAH KAIN DALAM MENINGKATKAN KETAHANAN PANGAN DI KELURAHAN TAMANSARI KECAMATAN TAMANSARI KOTA TASIKMALAYA - Mumu Mumu; Dede Anwar (Jurnal Abdimas Bina Bangsa, 2022)
The purpose of implementing this community service (PbM) is to assist and facilitate the community in improving food security through empowering women, especially mothers, in household economic activities to earn additional income in the family. Through this empowerment, they must be equipped with knowledge and skills in accordance with the needs of the business world, one of which is a food security program through the activity of making beds made from cloth waste.The type of output from community service activities (PbM) is expected to be able to reveal and help solve problems faced by the community, especially women or mothers, and realize the importance of skills to be able to empower themselves and empower the environment or the potential that exists in the area so that it can be of economic value. Another target to be achieved in this service is the substantive part related to the study of women's empowerment in alleviating poverty.Based on the findings in the field, information was obtained from them that the program implemented was deemed suitable for the community, especially women or mothers in the midst of limitations in recognizing their potential, so that most of them expected this activity to be carried out continuously in order to improve their skills. Furthermore, they hope that this program can be equipped with assistance in starting a business.The target set in community service for the food security scheme (PbM-KP) is to provide training to the community, especially women or mothers in Tamansari Village, Tamansari District. The program carried out is training to make beds made from cloth waste, with the hope that they will acquire skills to increase family income to maintain the stability of family food security